Contribution of multimedia software towards learning in open distance learning - Zoraini Wati Abas; Rosliza Othman; Santhanadass , Thangapragasam; P. Rajesh , Kumar (2007)
This paper highlights the use of an interactive multimedia software that have been specifically developed to teach a science course on basic techniques and laboratory safety in Open university Malaysia (OUM).